2011
DOI: 10.1063/1.3581071
|View full text |Cite
|
Sign up to set email alerts
|

Oxadiazole host for a phosphorescent organic light-emitting device

Abstract: Articles you may be interested inDistinguishing triplet energy transfer and trap-assisted recombination in multi-color organic light-emitting diode with an ultrathin phosphorescent emissive layer

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 36 publications
(35 reference statements)
0
7
0
Order By: Relevance
“…Oxadiazoles typically exhibit electron transporting characteristics which can be used as the host for phosphorescent OLEDs [ 28 31 ]. In our previous study, we demonstrated an efficient blue phosphorescent OLED consisting of iridium(III)bis[4,6-(di-fluorophenyl)-pyridinato- N ,C2′]picolinate (FIrpic) doped into 2-phenyl-5-(2′,4′,6′-trimethyl-[1,1′-biphenyl]-4-yl)-1,3,4-oxadiazole (OXD) possessing good electron transporting characteristics and a wide bandgap [ 32 ]. In this paper, we investigate the carrier injection and transport characteristics in the EML of such an OLED.…”
Section: Introductionmentioning
confidence: 99%
“…Oxadiazoles typically exhibit electron transporting characteristics which can be used as the host for phosphorescent OLEDs [ 28 31 ]. In our previous study, we demonstrated an efficient blue phosphorescent OLED consisting of iridium(III)bis[4,6-(di-fluorophenyl)-pyridinato- N ,C2′]picolinate (FIrpic) doped into 2-phenyl-5-(2′,4′,6′-trimethyl-[1,1′-biphenyl]-4-yl)-1,3,4-oxadiazole (OXD) possessing good electron transporting characteristics and a wide bandgap [ 32 ]. In this paper, we investigate the carrier injection and transport characteristics in the EML of such an OLED.…”
Section: Introductionmentioning
confidence: 99%
“…For 2CbzTAZ, electron mobility also exhibited a more increased slope than that of holes 23 . Therefore, with increasing voltage, the recombination zone in the EML shifts toward the anode side and the emission spectrum becomes redshift because of the microcavity effect inside the device 24,36 .
Figure 5EL spectra at different driving voltages for BPOLEDs with different hosts: ( a ) mCP, ( c ) TAZ, ( e ) mCP:TAZ, and ( g ) 2CbzTAZ. ( b ), ( d ), ( f ), and ( h ) are zoomed-in spectra at short wavelength region (380–460 nm) of ( a ), ( c ), ( e ), and ( g ), respectively.
…”
Section: Resultsmentioning
confidence: 99%
“…Organic light-emitting device (OLED) is advantageous to use as one of the most promising lighting technologies for the next generation due to its low cost, light weight, self-emission, wide view-angle [1,2]. Hence, its output efficiency and lifetime are critical factors for mass production [3]. Currently, the most efforts and reports focused on pursuing the high efficiency OLED, especially on blue OLED.…”
Section: Introductionmentioning
confidence: 99%